The Role of Civic Education in Building National Character in the Digital Era - Agnesia, Rahmita (International Journal of Students Education, 2025)
The purpose of this research is to find out the role of education in building the moral character of students in the modern era. The digital era marked by the rapid development of information and communication technology has a significant impact on various aspects of life, including the formation of national character. This study aims to examine the role of civic education in building national character in the digital era. Through literature studies and qualitative data analysis, this study shows that civic education has a crucial role in equipping the younger generation with national values, digital ethics, and critical thinking skills. This is the impact of globalization, on the other hand we have experienced the development of science and technology, besides that we can be creative in creating new innovations according to the development of science and technology and globalization. However, we do not remember the negative impact, namely the decline in social values due to the small impact of the increasingly advanced technology that exists today. However, challenges such as the rapid flow of information, hoaxes, and digital polarization require innovation in teaching methods and the development of civic education curricula.